Biomining: an Established and Dynamic Biotechnology - DAVID BARRIE JOHNSON (Indonesian Society for microbiology, 2012)
â€œBiominingâ€ is generic term to describe the application of living organisms to extract and recover metals from mineral ores and waste materials. Since its inception as a crude technology (â€œdump leachingâ€) for treating â€œrun of mineâ€ rocks and boulders that contained too little copper to be processed by conventional processing, engineering options usedÂ in biomining have becomeÂ increasinglyÂ refined and diverse. Currently, microbiological processing is used to extract both base metals (copper, and to lesser extents nickel and zinc) and precious metals (mostly gold) from ores and mineral concentrates in heaps and stirred-tank bioreactors, as well as in dumps. Recent developmentsÂ includeÂ the demonstration, at pilot-scale, ofÂ indrectÂ leaching of zincÂ sulfide concentrates,Â in which the biological step (regeneration of ferric iron) is carried out independently of abiotic mineral oxidation, andÂ using microbiologically-mediatedÂ reductiveÂ dissolutionÂ ofÂ ferricÂ iron mineralsÂ toÂ liberateÂ nickelÂ from lateritic ores.